Factors Affecting Job Satisfaction and Its Effect on Employee Resignation in the Mulia Health and Dental Care (MHDC) Clinic Group - Amanda Setiorini; Wiwik Rachmarwi (Sekolah Tinggi Manajemen IPMI, 2020)
This study wants to find out whether compensation, job safety, career paths, communication, relationships with superiors, and work-life balance affect job satisfaction, and how they affect employee resignation. From a population of 100 employees, a total of 73 people were sampled. The results show that compensation and work-life balance have a significant effect on job satisfaction and resignation, while relations with superiors have a significant effect on job satisfaction, and communication has a significant effect on resignation through job satisfaction.